2019
DOI: 10.1016/j.eurox.2019.100037
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among algometry, the visual analogue scale, and the numeric rating scale to assess chronic pelvic pain in women

Abstract: Objective To investigate the correlation between the numerical rating scale, visual analogue scale, and pressure threshold by algometry in women with chronic pelvic pain. Study design This was a cross-sectional study. We included 47 patients with chronic pelvic pain. All subjects underwent a pain assessment that used three different methods and were divided according to the cause of pain (endometriosis versus non-endometriosis). Moreover, we assessed the agreement betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…However, contrary to the VAS results there was no difference in pain pressure threshold one or two days following the foot march. The VAS and algometry have previously been shown to be correlated [43], however we found no significant correlation between the two measurements. These two measurements assess a different component of back pain, and the VAS may be a better assessment of LBP at low levels.…”
Section: Discussioncontrasting
confidence: 79%
“…However, contrary to the VAS results there was no difference in pain pressure threshold one or two days following the foot march. The VAS and algometry have previously been shown to be correlated [43], however we found no significant correlation between the two measurements. These two measurements assess a different component of back pain, and the VAS may be a better assessment of LBP at low levels.…”
Section: Discussioncontrasting
confidence: 79%
“…The main outcome measure was pain intensity. Pain intensity was registered using the 10-cm VAS, in which 0 represented “no pain” and 10 represented “the most intense pain imaginable.” This scale showed excellent reliability in chronic pain subjects, with an Intraclass Correlation Coefficient (ICC) of 0.97–0.99 [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The visual analog scale score is a time-proven subjective means of quantifying the pain of a patient [33,34] and has been shown to correlate with algometer findings in earlier studies [34][35][36]. This prospective study has shown that by knowing the pain threshold of an individual preoperatively, we can titrate the analgesic requirement for the patient postoperatively to enhance pain relief.…”
Section: Discussionmentioning
confidence: 99%